Football biomechanics - Hennig, E. (Ewald); Nunome, Hiroyuki; Smith, Neal 1972- (Routledge research in football, 2018)
Football Biomechanics explores the latest knowledge of this core discipline in sport science across all codes of the sport. Encompassing a variety of styles, including original scientific studies, syntheses of the latest research, and position statements, the text offers readers the most up-to-date and comprehensive reference of the underlying mechanics of high-level football performance.